Amputation and rehabilitation. Issue 2 (February 2019) - Guest, Francesca; Marshall, Colette; Stansby, Gerry
Abstract: Most lower limb amputations in the UK are performed in order to treat peripheral arterial disease and its complications. Amputations are usually classified as minor (toe and partial foot amputations) or major (when most of the limb is removed). Principles of selecting amputation level are considered and the importance of optimization of the patient's medical status is stressed. Most patients requiring amputations have significant comorbidities and amputation carries an appreciable anaesthetic risk. Minor amputations include toe and ray amputations, transmetatarsal and mid-foot amputations. Ankle-level amputations, such as Syme's amputation, are rarely indicated and it is difficult to fit prostheses to these stumps. Below-knee and above-knee amputations are the most commonly performed major amputations. Below-knee amputations may be carried out using either a long posterior flap or skewed flaps. Skewed flaps may be preferred when the posterior skin is of poor quality, and produce a cylindrical stump well-suited to limb fitting. Through-knee and hip disarticulations are also described. Successful amputation surgery, with good outcomes for the patient, requires attention to detail and careful coordination with physiotherapy and rehabilitation departments. The aim is to produce a well-healed, pain-free stump suitable for limb fitting.